FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR - Salim, Felisia; Setijaningsih, Herlin Tundjung (Jurnal Paradigma Akuntansi, 2024)
This study aims to determine and analyze the effect of liquidity, capital structure, and business risk on the company's financial performance in manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2020. The sample used in this research is 70 companies, which is the result of selection using purposive sampling method to obtain valid data. The data processing technique uses multiple regression analysis assisted by a computer-based program, namely Eviews (Economic Views) version 12. Based on the results of the F test the results of this study indicate that liquidity, capital structure, and business risk simultaneously (simultaneously) have a significant effect on company's financial performance. Based on the t-test (partial) the results show that liquidity and business risk have no positive and significant effect on the company's financial performance. Meanwhile, only the capital structure has a positive and significant effect on the company's financial performance.